A blockchain-based IIoT traceability system: ERC-721 tokens for Industry 4.0 - Koustas, Spyridon Georg; Jalowski, Max; Reichenstein, Tobias; Oks, Sascha Julian (Procedia CIRP, 2023)

A reference architecture for the operationalization of machine learning models in manufacturing - Raffin, Tim; Reichenstein, Tobias; Werner, Jonas; Kühl, Alexander; Franke, Jörg (Procedia CIRP, 2022)
Inherent characteristics of machine learning algorithms such as their probabilistic nature, their reliance on large datasets as well as their need for constant retraining pose major challenges to the operationalization of machine learning models (MLOps) in the manufacturing domain. As such systems are known to quickly accumulate technical debt due to system-level interdependencies of code, data, and models, clear abstractions boundaries are mandatory. Therefore, this publication derives a systematic functional decomposition of an MLOps system tailored to the manufacturing industry into specific domains and contexts. Moreover, a concrete deployment view is provided, and possible future research directions are discussed.<br

Bi-directional DC Charging Stations for EVs on renewable-powered LVDC Grids: Design, Sizing, Control and Testing - Gutwald, Benjamin; Lehmann, Raphael; Barth, Martin; Reichenstein, Tobias; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility, EPTS 2024, 2024)
E-mobility has undergone a remarkable transformation in recent years. It has progressed from the early days of a few electric vehicles (EVs) to widespread acceptance and integration into society. In the effort to address climate change, it has also become a necessity. The advancement in battery technology has enabled these EV not only to have better performance and longer ranges but also the capability to function as energy storage units for both households and businesses. This feature can prove valuable in industrial fleets, contributing substantially to grid stability and financial savings through temporary renewable energy storage and peak load balancing. DC grids provide the most flexible, efficient, and environmentally friendly charging architecture. Ideally, they are supplied directly from renewable energy generators. While bidirectional charging station prototypes for AC networks are emerging, solutions for future DC grids are still lacking.This publication evaluates the potential of this novel supply architecture and derives requirements for the regulatory-compliant design and commissioning of DC-coupled bidirectional direct current (DC) charge points (CPs). Furthermore, a proposal for the selection, dimensioning and interconnection of the electrical components, as well as the associated control and communication architecture of a corresponding power scalable charger is presented. This also includes the meaningful integration into an industrial DC grid, including the backend communication with the associated energy management system (EMS), which also plays a decisive role in the exploitation of the potential of the technology. In the first test phase of the charging station, a power-hardware-in-The-loop EV simulation will be carried out in conjunction with a regeneratively fed industrial low voltage direct current grid until standardized solutions for bidirectional EVs are actually available on the market.
CRIS-Team Scopus Importer:2024-08-02
Keywords: bidirectional charging; Direct current grid; LVDC; smart grid; V2G

Blockchain und digitaler Schatten: Potenzial und Herausforderungen für KMU - Koustas, Spyridon Georg; Reichenstein, Tobias (2023)

Comparative Efficiency Analysis in Recuperative Electrical Drives: A Study of LVDC vs. LVAC-Power Supply - Gutwald, Benjamin; Korneev, Aleksandr; Römer, Patrick; Barth, Martin; Reichenstein, Tobias; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility, EPTS 2024, 2024)
Electric drives account for a significant portion of the world's demand for electrical energy. The use of direct current (DC) machines or frequency-controlled operation of alternating current (AC) machines, which require rectification, can result in substantial material and operating energy savings, leading to reduced costs and CO2 emissions. Novel DC grids enable the use of braking energy, efficient integration of renewables and storage systems, and connection of additional grid participants. This eliminates many material-And energy-intensive conversion processes compared to conventional AC supply. To quantify these savings for electric drives, a prototype of a servo drive controller with a connected linear axis on a developed test bench was measured and analyzed. Then an efficiency comparison between AC and DC power supplies was conducted with over 240 measurements. Adjustable influencing parameters were the operating mode according to IEC 60034-1, the installation angle of the axis, the mass of the transported load as well as the accelerations and speeds. The comparison was conducted with a full factorial design of experiments, the results statistically evaluated, and critically reflected. By using the braking energy in DC operation and eliminating the rectifier stage, the energy consumption of the drive controller was reduced by 12-25 % compared to AC supply. In addition, the unfavourable design ratio results in high reactive power in AC operation. The study demonstrates the great potential for DC grids, which are currently still a rarity. Due to the lack of experience with DC grids, a second part of this publication series analyses international standards and proposes two different protection concepts for the safe and regulation-compliant integration of drives into the DC grid, that the practical commissioning of the concept is possible. In order to complete the efficiency comparison of the motor controller between AC and DC operation, the losses of the switching devices required for grid integration were also measured and the losses compared with established protection concepts for AC operation. In summary, this study analyses the potential of DC grids using the case of electric drives. It provides recommendations for engineers on designing energy-efficient power supplies.
CRIS-Team Scopus Importer:2024-08-02
Keywords: direct current; Electrical drives; energy efficiency; frequency converter; protection; recuperation; safety

Comparative Efficiency Analysis in Recuperative Electrical Drives: A Study of LVDC vs. LVAC-Protection Components and Grid Integration - Gutwald, Benjamin; Korneev, Aleksandr; Römer, Patrick; Barth, Martin; Reichenstein, Tobias; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Based on a full factorial metrological analysis, part 1 ("power supply") of the publication series demonstrates the great energy-saving potential for the operation of electric drives on the direct current (DC) grid. In the analysis, the energy requirement of a drive system with a DC supply could be reduced between 12 and 25 % compared to an alternating current (AC) supply. In order to realize the promising supply concept via a DC grid, a safe switching and protection concept is required to integrate the drive. Due to a lack of experience with powerful industrial DC grids, most planners and installers do not have the knowledge to plan and commission such electrical systems in accordance with regulations. In addition, the respective switching and protective devices influence the efficiency of the overall system. This publication offers decision-making aids for grid integration to enable the practical feasibility of the concept outlined in Part 1. It covers the selection and design of the protection concept. Specifically, two concepts for switching and protection of drive controllers on the DC-side, with different costs and safety standards, are proposed and compared to an established protection concept for AC supply. The proposals are based on relevant international standardization. Part 1 of this publication only considered the drive controller's electrical power consumption, but this section also measured and compared the load-dependent losses of each component of the associated protection scheme. Depending on the system voltage, power range and planning variant, the measured losses in AC operation are twice as high. The loss characteristics are made up of the ohmic losses with a quadratic gradient with the current flow and an offset due to the constant power requirement of the control circuit. Reactive power only occurs in the AC system and significantly increases the losses of the protective devices and the transmission system. Based on several test setups, this publication provides a holistic efficiency comparison for the DC-based energy supply of drive systems. It provides a design and decision-making aid for system planners, installers and commissioning engineers as well as investment management and thus makes a significant contribution to the roll-out of environmentally friendly DC grids.
CRIS-Team Scopus Importer:2024-08-02
Keywords: direct current; Electrical drives; energy efficiency; frequency converter; protection; recuperation; safety

Current Distribution Monitoring in Capacitor Discharge Welding - Meiners, Moritz; Reichenstein, Tobias; Franke, Jörg; Hauenstein, Rainer (2020)
The capacitor discharge welding (CDW) is a resistance welding process that excels through brief process times, low thermal stress, and good automation potential. Nevertheless, potential industrial users hesitate to use the CDW process, owing mainly to the unavailability of automated process control to ensure cost-efficient production and high product quality. For quality assurance, representative values or process curves of the most critical process parameters such as capacitor energy, contact force, electric current, and sink-in depth are monitored. The lack of full significance of this monitoring is indicated by the regular destructive testing of random samples through load tests and cross-section analysis. The essential aspect of the process quality is heat development in the welding zone. The current distribution, as one crucial parameter influencing heat development, is missing. Therefore, this paper presents an in-situ qualitative, indirect current distribution measurement system. The new measurement supplements the process monitoring and analysis, and thus, gain new process knowledge. With better process monitoring and thus understanding, new application areas can be developed for CDW.<br
Keywords: capacitor discharge welding; current distribution monitoring; sensor system; resistance welding; hall effect sensor

Data-Driven Bed of Nails Wear Analysis for the in-Circuit-Testing of Electronic Modules - Sindel, Till; Thielen, Nils; Mahr, Felix; Reichenstein, Tobias; Erdogan, Hüseyin; Franke, Jörg (2024 IEEE 29th International Conference on Emerging Technologies and Factory Automation (ETFA), 2024)
In order to optimize the timing of maintenance operations, this work aims at laying the foundation for applying predictive maintenance strategies for the In-Circuit-Test (ICT) by proposing a data analysis pipeline for capturing wear impact on process data. The ICT is an established inspection process within the electronic module production. Subsequently to the assembly of components on a printed circuit board (PCB) mainly using the surface mount technology (SMT) and through hole technology (THT), parts are tested for their conformity of electrical characteristics to predefined tolerances, as well as logical functionalities. Thereby, the ICT is conducted by physically connecting an adapter containing a bed of nails to the circuits of the assembled part and subsequently measuring component dependent characteristics such as the electrical resistance, impedance, inductivity and capacity. Due to the mechanical and electrical impact on the probes and the high-volume nature of the process, these temporarily connected components are subject to wear. Conventional maintenance approaches follow a scheduled preventive strategy by conducting maintenance operations following a predefined number of cycles or strokes. Due to the heuristic nature of the scheduling, the wear margin is not fully exploited and therefore additional costs for prematurely replacing the probes or the complete bed of nails occur. The findings for a real-world dataset from high-volume electronics production show temporal shifts in data distributions between maintenance operations, suggesting adapter-wide needle degeneration. Considering PCB and component batch effects is proposed for successive research methodologies in order to improve the accuracy of the approac

Demonstrating industrial smart product-service systems: Industry 4.0 maturity through stakeholder-oriented development and testing - Koustas, Spyridon Georg; Reichenstein, Tobias; Oks, Sascha Julian; Fuchs, Jonathan; Möslein, Kathrin (Procedia CIRP, 2023)

Demonstratoren im Industrie 4.0-Kontext - Dörr, Luca; Oks, Sascha Julian; Trezl, Jonas; Reichenstein, Tobias; Koustas, Spyridon Georg; Lehmann, Claudia (wt Werkstattstechnik - Online, 2024)
Industrie 4.0 bringt neben vielen Potenzialen auch eine erhebliche Komplexitätssteigerung mit sich. Um dieser effektiv zu begegnen, bieten Demonstratoren einen wertstiftenden Beitrag. Ihr Einsatz ermöglicht eine nutzerzentrierte Systementwicklung mit einhergehender Komplexitätsreduktion durch Modellierung und Simulation. Dieser Beitrag untersucht ihre Potenziale am Beispiel des Projektes „ConSensE“ mit Fokus auf Sensortechnologien und deren Nachrüstun
Keywords: Mensch und Technik; Produktionsarbeit; Sensoren

Four Independent Knowledge Domains to Enable an Agile, Distributed Development of User-Centred Engineering Configurators - Schäffer, Eike; Mayr, Andreas; Reichenstein, Tobias; Shafiee, Sara; Franke, Jörg (Procedia CIRP, 2021)
Robot-centric automation solutions (RAS) promise greater efficiency and consistent quality in production, relieving workers of physically demanding and dangerous tasks, especially in the times of COVID-19. Nevertheless, due to their relatively high complexity and implementation costs, RAS are only used to a limited extent by small and medium-sized manufacturing companies. As a rule, the high costs of RAS arise from custom engineering efforts, which take up to 70 percent of the acquisition costs. For this reason, it is necessary to optimise the engineering of RAS. However, software tools such as configurators have been used primarily for the individualisation of products, such as automobiles or clothing, based on variants predefined by the manufacturer, and less for the engineering of automation solutions. The development of knowledge-based systems, in particular knowledge-based engineering configurators (EC), is usually performed by few proficient experts with high development effort. One of the primary challenges in the knowledge acquisition is that several experts possess partial aspects of knowledge in an inhomogeneous, implicit form. Furthermore, there is a lack of efficient development methods for EC. By reusing knowledge elements from previous development projects, a sustainable increase in efficiency is possible. In order to enable an efficient development process of EC, we introduce a structuring model consisting of four knowledge domains (KD): knowledge about specific business cases (KD1), Best Practices as case-specific solution knowledge (KD2), logical expert knowledge (KD3) as well as semantically consistent data models for interoperability of different IT systems (KD4). As the four KD are independent, their development can be agilely divided among several teams or companies. Finally, the agile development approach is validated individually for each KD as well as comprehensively within the scope of the ROBOTOP platform for planning RAS.
Keywords: Best Practice; configurator; knowledge-based; knowledge acquisition; KBEC; engineering; planning; division of labour; automation; robot

From connectivity via intelligence toward sustainability? Maturity of shopfloor automation technology in the manufacturing industry - Reichenstein, Tobias; Reich, Christina Stefanie; Hoffmann, Kilian; Franke, Jörg (Procedia CIRP, 2024)
The manufacturing industry is experiencing a significant transformation driven by digital technologies, Industry 4.0 concepts, and the potential for sustainable practices. This research presents an overview of the manufacturing industry, focusing on the design of manufacturing systems, digital transformation, and sustainability, identifying the gap between technological advancements and their application in industrial settings. In order to examine this, a panel survey of 899 industrial participants was conducted. This analysis assesses the potential for automation and digital factory implementation alongside the dedication for sustainability in the manufacturing industry. The findings indicate that while research has advanced in these areas, practical applications in the manufacturing industry still lag behind, particularly in terms of technology readiness levels and data implementation for automation. This paper serves as a foundation for future research, providing insights into technologies ready for industrial implementation and identifying areas requiring further optimization and study. Therefore, a matrix is presented that aids in selecting or strategizing technology utilization during the design of manufacturing systems. However, this research primarily focused on technological aspects, recommending future research to explore the interplay between organizational, human related factors, and technology to design manufacturing systems successfully with respect to sustainabilit
Keywords: Industry 4.0; shopfloor automation; digital factory; digital twin; sustainability; Design methodology; tools; technologies

Implementation of Machine Vision based Quality Inspection in Production: An Approach for the Accelerated Execution of Case Studies - Reichenstein, Tobias; Raffin, Tim; Sand, Christian; Franke, Jörg (Procedia CIRP, 2022)
The implementation of machine vision based quality inspection systems increases productivity and reduces human error during visual inspection, thus improving product quality. During the planning process of these inspection systems, case studies are executed to evaluate and ensure applicability, which so far has been an iterative and inefficient process due to the lack of existing methodologies and guidelines. Therefore, this paper presents a holistic approach for efficiently executing case studies to plan and implement machine vision based quality inspection systems in production. An evaluation via an industrial use-case resulted in a significantly quicker planning process.<br

Intelligente Energieoptimierung für nachhaltige Produktionssysteme - Schneider, Alexander; Barth, Martin; Müller, Alexander; Reichenstein, Tobias; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2025)
In der industriellen Produktion ist die Steigerung der Energieeffizienz und die damit verbundene Reduktion von CO₂-Emissionen eine der zentrale Herausforderungen in Zeiten des Klimawandels. Besonders in energieintensiven Industrien ist eine optimierte Energienutzung unerlässlich. Der Beitrag untersucht Strategien zur nachhaltigen Energienutzung wie die Modellierung und Simulation von Energieverbräuchen zur Lastspitzenreduktion sowie die dynamische Anpassung der Produktionsphasen mithilfe maschinellen Lernens. Zudem werden Ansätze zur Auftragsplanung und -verteilung beschrieben, die durch Deep Reinforcement Learning optimiert werden, um Prozesse an erneuerbare Energien anzupassen. Digitale Zwillinge und detaillierte Energieüberwachung helfen, Ineffizienzen frühzeitig zu erkennen und zu korrigiere
Keywords: Energieeffizienz; CO₂-Emissionsreduktion; Dynamische Produktionsanpassung; Optimierung; Künstliche Intelligenz

Measurement Technology in Industrial Low Voltage DC grids-Requirements and Selection Procedure - Gutwald, Benjamin; Reichenstein, Tobias; Barth, Martin; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility, EPTS 2024, 2024)
Companies are increasingly looking for opportunities to reduce their energy consumption and move toward carbon-neutral production. Recent research has shown the high potential of direct current (DC) smart grids in production plants. Although they promise increased system efficiency and simplified integration of renewable energy sources or storages, there is still a lack of knowledge among product developers and production planners regarding the integration of DC grid components. Since measurement devices perform a variety of tasks, their implementation poses an even greater challenge to planners. Therefore, this paper systematically analyses different measurement use cases in terms of requirements, possible physical measurement principles, and sensor types. The results provide support for production planners and electrical product developers, improving the technology diffusion and shortening the planning times. Furthermore, a developed systematic selection procedure assists planners. The lower barrier for technology transfer to industry leads to a faster exploitation of the potential of DC powered production facilities.
CRIS-Team Scopus Importer:2024-08-02
Keywords: direct current grid; energy measurement; sensors

Modeling and Simulation Techniques for Energy Behavior in Production Systems: A Review and Systematic Taxonomy - Barth, Martin; Russwurm, Eva; Gutwald, Benjamin; Kunz, David; Reichenstein, Tobias; Franke, Jörg (2023 IEEE 2nd Industrial Electronics Society Annual On-Line Conference (ONCON), 2023)
So far, existing publications related to energy simulation of production systems predominantly focus on application or simulation aspects, with a particular emphasis on discrete event simulation (DES) of process chains. However, the modeling of energy aspects, even beyond the typical DES area, is crucial for a successful simulation project in terms of analyzing and optimizing energy-saving potentials within the industry. Therefore, this paper focuses on major techniques used to model the energy behavior of production systems across all levels of production systems, from individual components to a network of factories. Through a structured literature review, we identified the primary modeling techniques and typical characteristics for energy modeling and structured them in the form of a taxonomy.<br
Keywords: Industries; Industrial electronics; Production systems; Systematics; Taxonomy; Production facilities; Behavioral sciences; Modeling; Simulation; Energy Efficiency

Qualitative assessment of the impact of manufacturing-specific influences on Machine Learning Operations - Raffin, Tim; Reichenstein, Tobias; Klier, Dennis; Kühl, Alexander; Franke, Jörg (Procedia CIRP, 2022)
Machine Learning Operations (MLOps) enables the streamlining of the development and deployment processes of machine learning models; thus, manufacturers can utilize the inherent flexibility and adaptability of Deep Learning at scale to further optimize their processes. This publication provides insights into the challenges that companies face while striving for the efficient operationalization of machine learning algorithms. Moreover, a mapping of capabilities and requirements is presented to provide a baseline for the qualitative analysis of the current state of the art. In conclusion, this article discusses the shortcomings of the existing literature and provides novel implications for MLOps systems in manufacturing.<br

Qualitative in-situ-Stromflussmessung der Schweißzone/Qualitative in-situ current flow measurement of the weld zone - Reichenstein, Tobias; Scheck, Albert; Franke, Jörg; Meiners, Moritz (wt Werkstattstechnik - Online, 2024)
Das Kondensatorentladungsschweißen ist ein Widerstandsschweißverfahren, das sich durch kurze Prozesszeiten und gutes Automatisierungspotenzial auszeichnet. Bisher erfasste Kenngrößen der Prozessüberwachung ermöglichen keine signifikanten Aussagen zur Gleichmäßigkeit der Verbindungsqualität. Dieser Beitrag stellt ein qualitatives in-situ-Stromflussmesssystem vor, welches das bisherige Prozessmonitoring ergänzt, den Aufbau von neuem Prozesswissen ermöglicht und durch das verbesserte Prozessverständnis neue Anwendungsfelder für das KE-Schweißen erlaub

Reference Architecture and Agile Development Method for a Process-Driven Web Platform based on the BPMN-Standard and Process Engines - Schäffer, Eike; Schobert, Marvin; Reichenstein, Tobias; Selmaier, Andreas; Stiehl, Volker; Herhoffer, Markus; Mala, Matûs; Franke, Jörg (CIRPe 2021 Sustainable, resilient, and agile manufacturing and service operations: Lessons from COVID-19, 2021)
One of the major trends in the 21st century is the trend towards digital transformation within Industry 4.0. In order to adapt to high volatile market conditions, especially in the context of COVID-19, companies do not only have to transfer their knowledge into digital systems. Furthermore, they have to be able to tailor their business processes rapidly to changing customer’s needs. The implementation of efficient and transparent processes is thereby known as the process of digital transformation and requires its underlying software-architecture to be highly flexible and scalable. Especially a web-based platform represents a highly user-centered application for multi-user purposes and can quickly adapt to its customer needs. While e-commerce and video-streaming platforms, like eBay or Netflix, often already provide a highly flexible, microservice-based architecture, common tools and platforms within the engineering-domain are usually still based on rather monolithic or service-oriented architectures (SOA). Therefore, an adaption to changing market conditions and the integration of proprietary tools is often technically demanding and economically not feasible, especially for small and medium-sized enterprises (SME). In this context, the so-called Process-Driven-Approach (PDA) offers a sustainable and tool-neutral blue-print for a system’s architecture strictly following the separations-of-concerns principle and allowing a user-centered layout. The PDA enables the integration of business processes and tools within an orchestrating framework, provided by a process engine. While the PDA within the engineering domain has been presented in a preceding paper, this paper supposes a reference architecture and agile development method for engineering-platforms via the PDA based on the BPMN-standard and process engines. These concepts are validated by a prototypical implementation of a platform-demonstrator for tool-supported planning of robot-based automation solutions.<br
Keywords: Process-Driven web platform; reference architecture; ROBOTOP; Process-Driven-Approach; PDA; agile; user-centered; development method

Sustainable manufacturing practices: A systematic analysis and guideline for assessing the industrial Product Carbon Footprint - Gutwald, Benjamin; Baumann, Nicolas; Funk, Felix; Reichenstein, Tobias; Albayrak, Baris; Franke, Jörg (2024 1st International Conference on Production Technologies and Systems for E-Mobility, EPTS 2024, 2024)
Climate protection has gained significant political and social relevance in the corporate sphere. On the one hand, industry bears a special responsibility towards reducing greenhouse gas (GHG) emissions. On the other hand, adopting sustainable practices presents multiple economic opportunities that surpass mere image and efficiency factors. In various industries, the carbon emissions associated with specific products are becoming a crucial factor in purchasing decisions. One example is the automotive industry, where original equipment manufacturers (OEMs) are increasingly looking to track and manage the carbon footprint of their products throughout the supply chain. Moreover, regulatory requirements obligate companies to measure their products' GHG emissions. This includes the EU's Battery Passport Initiative. From 2026, all batteries installed in electric vehicles must provide basic sustainability-related information, including transparent documentation of their carbon footprint. This shows that the Product Carbon Footprint (PCF) has become a crucial business indicator, increasingly influenced by Life Cycle Assessment (LCA) methodologies. However, obstacles remain with data collection and GHG emission accounting. Comprehensive standards and guidelines exist for the quantitative determination and reporting of GHG emissions. Nonetheless, quantifying the PCF presents challenges for many companies. This is due to high complexity, insufficient data as well as diverse methodologies and the lack of a mandatory standard. Hence, a valid comparison of the results is not always feasible. This publication provides a survey and classification of various standards and software-based solutions for calculating the PCF, integrating LCA principles. The analysis' requirements profile is shaped by international regulations, economic, and political trends. To tackle the primary challenges in PCF determination, essential research trends and solutions are compiled based on a literature review. The final outcomes are presented in the form of a practical guide, assisting users in measuring, and communicating product specific GHG emissions in manufacturing throughout the supply chain.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Carbon Footprint; Greenhouse Gas Protocol; ISO 14067; Life Cycle Assessment; PCF; Sustainable manufacturing

Toward a structured concept for purpose-driven modeling of a digital shadow in manufacturing - Reichenstein, Tobias; Koustas, Spyridon Georg; Roßner, Alexander; Meiners, Moritz; Franke, Jörg (Procedia CIRP, 2023)
The growing relevance of Industry 4.0-related technologies and the transformation toward service-oriented business models in manufacturing requires relevant, high-qualitative data. The digital representation of operation and manufacturing under a specific purpose is called a digital shadow (DS). Although this purpose represents the decisive factor between different digital shadows, its systematic determination has been addressed insufficiently. Therefore, this paper presents a systematic, purpose-driven modeling approach for the digital shadow supporting manufacturing companies in developing a data basis for applications. This approach is applied to a crimping machine as an example and will be optimized in future evaluations.<br